ENTERITIS AND SECONDARY INFECTION COCCIDIOSIS IN BROILER CHICKEN AT TEGAL, CENTRAL JAVA - Qomariyuti, Refina Sastya; Majid, Rully Abiyoga; Amany, Nafisa Raihana; Fajrin, Rizni Fania; Tyagita, Tyagita; Viqih, Muhammad (Buletin Veteriner Udayana, 2023)
Excessive chlorination in chicken drinking water can trigger pathogenic microbial infection, such as Eimeria protozoa infection which causes coccidiosis. This disease can cause losses in farmers because it causes poor weight gain and high mortality. In this study, it was known that broiler chicken on farm in Tegal were reported with inappetence, lethargy, weakness, paleness and bloody diarrhea. Water examination was performed and found 600 ppm chlorine in the drinking water and the litter thickness was less than 5 cm. Post mortem examination found enlargement of the heart and kidney, caecal tonsil and caecal bleeding, swelling of the intestine and enteritis. Based on that pathological anatomy lesion and examination of oocysts per gram of feces, the chicken diagnosis as enteritis followed by coccidiosis as a secondary infection due to Eimeria tenella with a severe infection. Therefore, control can be carried out by giving Capzuril® or Agricox®, vitamin K, vitamin A and probiotics and prevention by controlling the chlorination of the drinking water and increasing the thickness of the litter.